Is the treatment with biological or non-biological DMARDS a modifier of periodontal condition in patients with rheumatoid arthritis? (2020)
Background and objective: Experimental models suggest the use of different therapy protocols in rheumatoid arthritis (RA) as modulators on periodontal condition. This study evaluated the effects of conventional drug treatment and anti-TNF therapy in patients with RA on microbiological and periodontal condition, establishing the association of markers of periodontal infection with indexes of rheumatic activity. Materials and methods: One hundred seventy nine individuals with RA were evaluated (62 with anti-TNF-. and 115 with only DMARDs). The periodontal evaluation included plaque and gingival indexes, bleeding on probing (BOP), clinical attachment loss (CAL), pocket depth (PD) and subgingival plaque samples for microbiological analysis. Rheumatologic evaluations included a clinical examination, rheumatoid factor (RF), antibodies against cyclic-citrullinated peptides (ACPAs), and activity markers (DAS28-ERS), high sensitive C-reactive protein (hs-CRP), erythrocyte sedimentation rate (ESR). Results: Anti-TNF-alpha therapy influenced periodontal microbiota with a higher frequency of T. denticola (p=0.01). Methotrexate combined with leflunomide exhibited a higher extension of CAL (p=0.005), and anti-TNF-alpha therapy with methotrexate was associated with a lower extension of CAL (p=0.05). The use of corticosteroids exerted a protective effect on the number of teeth (p=0.027). The type of DMARD affected P. gingivalis, T. forsythia and E. nodatum presence. Elevated ACPAs titers were associated with the presence of red complex periodontal pathogens (p=0.025). Bleeding on probing was associated with elevated CPR levels (p=0.05), and ESR was associated with a greater PD (p=0.044) and presence of red complex (p=0.030). Conclusion: Different pharmacological treatments for RA affect the clinical condition and subgingival microbiota.